Improved UMHexagonS Algorithm and Architecture for Low Power H.264 Video Compression - Arief Affendi Juri (School of Microelectronic Engineering, 2013)
This objectives of this research are to propose a new low complexity ME algorithm with better performance especially in its computational speed and to propose a new ME architecture that able to reduce the energy consumption of the module.